2019
DOI: 10.1002/mrd.23154
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐210 regulates human trophoblast cell line HTR‐8/SVneo function by attenuating Notch1 expression: Implications for the role of microRNA‐210 in pre‐eclampsia

Abstract: Successful pregnancy depends on the precise regulation of extravillous trophoblast cell invasion ability. MicroRNA‐210‐3p (miR‐210), which is increased in the placenta of pre‐eclampsia. Furthermore, miR‐210 could inhibit trophoblasts invasion and might act as a serum biomarker for pre‐eclampsia. Previous studies have demonstrated that miR‐210 regulates HUVEC (human umbilical vein endothelial cell)‐mediated angiogenesis by regulating the NOTCH1 signaling pathway. Studies by our group have previously identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…It is widely accepted that excessive apoptosis and poor invasion of trophoblast cells serve major roles in the pathogenesis of PE. Wang et al reported that regulation of the microRNA-210/NOTCH1 signaling pathway attenuated the impaired HTR-8/SVneo cell proliferation, migration and invasion, which contributed to trophoblast dysfunction in the placenta of patients with PE (27). This is consistent with the data of the present study, which indicated that downregulation of ANGPTL8 increased the viability and proliferation of HTR8/SVneo cells (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…It is widely accepted that excessive apoptosis and poor invasion of trophoblast cells serve major roles in the pathogenesis of PE. Wang et al reported that regulation of the microRNA-210/NOTCH1 signaling pathway attenuated the impaired HTR-8/SVneo cell proliferation, migration and invasion, which contributed to trophoblast dysfunction in the placenta of patients with PE (27). This is consistent with the data of the present study, which indicated that downregulation of ANGPTL8 increased the viability and proliferation of HTR8/SVneo cells (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…In another study, up-regulation of miR-210 reduced Notch1 expression; impaired HTR8/SVneo proliferation, migration, invasion, and tubule formation; and promoted apoptosis; down-regulation of miR-210 had the opposite effects. These findings suggest that miR-210 plays a role in trophoblast dysfunction by reducing Notch1 expression (Wang R. et al, 2019).…”
Section: Roles In Trophoblast Cell Invasionmentioning
confidence: 76%
“…In general, Each miRNA has multiple target genes, such as miR-210, which not only targets HSD17B1s (Song et al, 2015), but also targets PTPN2 , KCMF1 (Luo et al, 2014), THSD7A (Tian et al, 2020), and Notch1 (Wang R. et al, 2019) to regulate the biological function of trophoblast and participate in vascular remodeling, growth and tube formation. Besides, several miRNAs also target the same gene.…”
Section: Roles In Immune Regulation and Inflammationmentioning
confidence: 99%
“…In view of the role of miR-210 in PE, related studies with larger sample sizes further confirmed that the placental expression of miR-210 in patients with PE did indeed increase significantly compared to the corresponding levels experienced during normal pregnancy [ 18 20 ]. miR-210 can inhibit the proliferation, invasion, and angiogenesis of trophoblasts by acting on the downstream target genes that encode KCMF1 [ 20 ], NOTCH1 [ 21 ] and MAPK [ 18 ]. Upregulated levels of miR-210 have also been detected in peripheral blood serum [ 18 ].…”
Section: Mirnas and Preeclampsiamentioning
confidence: 99%